INITIATION OF ECONOMIC TRANSFORMATION AT BRAJA GEMILANG BASED ON PRA: EMPOWERMENT MODEL FOR SUSTAINABLE DEVELOPMENT - Agus Subagyo; Elly Lestari Rustiati; Priyambodo; Desta Sendora; Dian Neli Pratiwi; Agus Wahyono; Suwarno (Jurnal Abdisci, 2026)
Braja Gemilang, Braja Selebah, East Lampung, has great natural and social resource potential, but has not been explored optimally. Participatory Rural Appraisal (PRA) was applied as the main approach to explore the potential local economy that is environmentally friendly, form business groups, and develop partnership networks. Activities conducted in July – August 2025 included participatory mapping, focus group discussions, comparative study visits, and partnership facilitation for three priority ventures: mocaf/tiwul, cassava-based flour production, organic fertilizer, and sumatran rhino food plant nursery. The initial output includes the formation of business groups (mocaf house), initial collaboration. The PRA-based mentoring model and approach showed support in both local welfare and conservation.